The sources of a practice code of ethics for nurses. - Davis AJ (Journal of Advanced Nursing (Wiley-Blackwell))
Interviews with a convenient sample of 27 master's-prepared nurses working in two clinical settings revealed that none of them knew the content of the American Nurses' Association Code for Nurses. A content analysis developed four sensitizing experiences that were sources for their code of nursing practice. These were categorized as: (a) clinical, (b) personal, (c) research, and (d) professional socialization as a student.